Formation of masculinity in Nedim Gürsel's Yüzbaşının Oğlu*. Issue 1 (2nd January 2017) - Alkan, Burcu
ABSTRACT: Issues of masculinity and sexuality in their various guises have been recurrent themes in the fiction of Nedim Gürsel, a contemporary Turkish novelist based in Paris. His latest novel, Yüzbaşının Oğlu (The son of the captain, 2014), which is recently translated into French ( Le fils du capitaine, 2016), combines the two themes most prominently. As the aged protagonist of the novel recounts the memories of the critical moments in his life, his story from childhood to adolescence is disclosed through a first-person narration. Beginning with the early loss of his mother and his emotional distance from his military officer father, his feelings of loss, abandonment, and loneliness are highlighted. His timid introduction to sexuality at boarding school marks his conception of manhood. This paper traces the foundations of his unsettled masculinity, shaped by an uneasy perception of sexuality in order to examine his scarred psychology.